Structure-guided mutagenesis of active site residues in the dengue virus two-component protease NS2B-NS3 - Salaemae, Wanisa (BioMed Central, 2010)
BACKGROUND: The dengue virus two-component protease NS2B/NS3 mediates processing of the viral polyprotein precursor and is therefore an important determinant of virus replication. The enzyme is now intensively studied with a view to the structure-based development of antiviral inhibitors. Although 3-dimensional structures have now been elucidated for a number of flaviviral proteases, enzyme-substrate interactions are characterized only to a limited extend. The high selectivity of the dengue virus protease for the polyprotein precursor offers the distinct advantage of designing inhibitors with exquisite specificity for the viral enzyme. To identify important determinants of substrate binding and catalysis in the active site of the dengue virus NS3 protease, nine residues, L115, D129, G133, T134, Y150, G151, N152, S163 and I165, located within the S1 and S2 pockets of the enzyme were targeted by alanine substitution mutagenesis and effects on enzyme activity were fluorometrically assayed. METHODS: Alanine substitutions were introduced by site-directed mutagenesis at residues L115, D129, G133, T134, Y150, G151, N152, S163 and I165 and recombinant proteins were purified from overexpressing E. coli. Effects of these substitutions on enzymatic activity of the NS3 protease were assayed by fluorescence release from the synthetic model substrate GRR-amc and kinetic parameters K(m), k(cat )and k(cat)/K(m )were determined. RESULTS: Kinetic data for mutant derivatives in the active site of the dengue virus NS3 protease were essentially in agreement with a functional role of the selected residues for substrate binding and/or catalysis. Only the L115A mutant displayed activity comparable to the wild-type enzyme, whereas mutation of residues Y150 and G151 to alanine completely abrogated enzyme activity. A G133A mutant had an approximately 10-fold reduced catalytic efficiency thus suggesting a critical role for this residue seemingly as part of the oxyanion binding hole. CONCLUSIONS: Kinetic data obtained for mutants in the NS3 protease have confirmed predictions for the conformation of the active site S1 and S2 pockets based on earlier observations. The data presented herein will be useful to further explore structure-activity relationships of the flaviviral proteases important for the structure-guided design of novel antiviral therapeutics.